Flood-Flow Characteristics Of Equatorial Natural Rivers In Sarawak, Malaysia - Lai, S.H.; Nabil, Bessaih; Law, P.L; Nor Azazi, Zakaria; Aminuddin, Ab. Ghani; Mah, D.Y.S. (The Institution of Engineers, Malaysia, 2008)
A study on two natural rivers during flood events located in the outskirt of Kuching city, Sarawak is carried out. This paper presents the results obtained from the field measurements, including velocity distributions, stage discharge relationships, roughness behaviours and discharge estimation. These have illustrated a large difference in velocity between the main channel and floodplain under flood conditions, and the effects of momentum transfer between deep and shallow flow, which include reduction in main channel velocity and discharge capacity, leading to a reduction in compound section capacity at depth above bankfull. Another significant characteristic for flow in natural rivers is that the floodplain regions are found to behave as a storage reservoir instead of conveying excess water. Flow resistance relationships have been presented in terms of Manning’s coefficient and Darcy-Weisbach friction factor, showing the complex nature of flow resistance in flooded natural rivers and further explaining the danger inherent in the conventional practices of extrapolating inbank data for the analysis of overbank flows. Results for discharge estimation have been shown for comparison with actual data, the errors incurred by applying empirical methods to compound channel flows have been quantified and found to depend on the particular method used.